Takhrij and Syarah Agrotechnology Hadith: Study of Black Seed, Healer of All Diseases - Wahid Saepul; Wahyudin Darmalaksana; Salamet Ginandjar (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith regarding the Black Seed which is used as a medicine for all diseases in the modern era. This research method is a qualitative type through literature and field studies with the approach of takhrij and sharah hadith. The results and discussion of this research is Black Seed is a versatile medicine from the time of the Prophet to the present, even in ancient Egypt, Black Seed was used as a corpse preservative. The conclusion of this research is that takhrij and sharah hadith about habatussauda provide extensive information to be developed in the modern era with an agrotechnological approach.